Pilomatricoma: A dermal analog of calcifying odontogenic cyst - Kaveri H; Punnya A (Wolters Kluwer Medknow Publications, 2008)
Pilomatricoma, also known as "Calcifying Epithelioma of Malherbe" is an uncommon, benign, cutaneous tumor originating from the hair matrix. Most often, its precise preoperative diagnosis is not possible. Rarity of this lesion and its histological resemblance to the calcifying odontogenic cyst (the Gorlin′s cyst) make it relevant, both to the maxillofacial surgeons and the pathologists. Here, we describe a case of pilomatricoma of the periorbital region in a young Indian female patient. We believe that its inclusion is essential in the differential diagnosis of hard masses of the maxillofacial and paraoral regions.